Other Side of Breast Cancer: Factors Associated with Caregiver Burden - Maryam Vahidi, PhD Student; Nader Mahdavi, PhD Candidate; Elnaz Asghari, PhD Candidate; Hossein Ebrahimi, PhD; Jamal Eivazi Ziaei, MD; Mina Hosseinzadeh, PhD Candidate; Hossein Namdar Areshtanab, PhD; Iraj Asvadi Kermani, MD (Elsevier, 2016)
Purpose: This study aimed to determine factors associated with caregiver burden among primary caregivers of women with breast cancer in Iran. Methods: This was a descriptive correlation study conducted in 2012 on 150 main caregivers of patients with breast cancer who came to the oncology clinic of Shahid Ghazi hospital in Tabriz, Iran. A questionnaire which included caregiving-related factors and the Zarit Burden Interview was used for data collection after its validity and reliability were determined. Data was analyzed using SPSS 13.0 software with descriptive and analytic statistics. The association between significant variables and the dependent variable with an observation of the effects of other variables was assessed using the multiple linear regression model. Results: The mean age of caregivers was 39.60 ± 13.80 years old, and 77 (51.3%) of them were men. The mean score of the Zarit Burden Interview was 30.55 ± 19.18. In the regression model, the mean score of activities of daily living, level of education, gender, and financial status were identified as the determining factors of the burden of caregivers. Conclusions: Primary caregivers need to be financially supported by the relevant organizations. Care skills training and providing palliative care seem helpful in reducing the pain and the burden of family caregivers for patients with breast cancer.